The Influence of Ethics and Fraud Triangle Components on Employee Fraud - Erik Ridha Nugraha; Heru Kurnianto Tjahjono; Majang Palupi (Jurnal Manajemen Universitas Bung Hatta, 2026)
This study aims to identify and review the articles systematically regarding the mediating effect of job satisfaction (JS) in the relationship between work life balance (WlB), perceived organizational support (PoS), and employee engagement (EE), particularly in the context of organizations and millennial generation employees. The approach used was a Systematic Literature Review (SLR) following the PRISMA 2020 guidelines and the Watase Uake Tools. The article identification process was carried out through the Scopus database and other additional sources (Google Scholar, ResearchGate, and campus repositories). The search keywords involved a combination of: “work life balance” , “perceived organizational support” , “employee engagement” , and “job satisfaction”, with a publication year range of 2015–2025. A total of 169 articles were identified from Scopus, and after a rigorous screening process, 27 articles were deemed eligible and analyzed in this review. The review results show that JS consistently acts as a mediating variable that strengthens the relationship between WlB and PoS support on EE. The selected articles support that WlB and PoS have a significant indirect influence on EE through JS. Job satisfaction as a driver of employee engagement, particularly among millennials.